Colorimetric evaluation, scanning electron microscopy and ?-EDXRF spectrometry of enamel whitened with violet light combined with carbamide or hydrogen peroxide - Antonialli, Fernanda; Gobbo, Vanessa; Kury, Matheus; Silva, Daylana da; Soares, Luis; Giannini, Marcelo (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
The aim of this study was to evaluate in vitro color change, surface morphology and mineral content of enamel submitted to bleaching with violet LED(LED) combined or not with 35% hydrogen(HP) or 37% carbamide peroxide(CP). Bovine crowns stained with black tea were randomly distributed into whitening groups(n=10): LED/HP, HP, LED/CP, CP, LED and C – control. Color change(?E, ?L, ?a e ?b) was spectrophotometrically determined among staining and 14 days elapsed from bleaching. Enamel surface was analyzed by means of SEM. Sixty additional enamel blocks were obtained, polished and submitted to initial surface michorhardness(KHN) for selection. One week elapsed from interruption of same protocols, calcium to phosphorous ratio(Ca/P) was determined under ?-EDXRF spectrometry. ?E, ?L and Ca/P ratio were tested with two-way ANOVA and Tukey’s test. ?a e ?b were evaluated under Kruskal-Wallis and Mann-Whitney tests(?= 5%). Although ?E and ?b were comparable among LED/HP and HP(p>0.05), CP’s was lower than LED/CP(p